2010
DOI: 10.1007/s00449-010-0466-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of spray drying process for Bacillus thuringiensis fermented wastewater and wastewater sludge

Abstract: Response surface methodology was used to optimize spray drying process for producing biopesticide powders of Bacillus thuringiensis by using fermented broth of starch industry wastewater and wastewater sludge. Analysis of variance was carried out using number of viable spores in the powder as dependent variable. The determination coefficients of models were 92 and 94% for fermented broth of starch industry wastewater and wastewater sludge, respectively. Under the optimal conditions of the operational parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…2006). However, shelf‐stable and effective products of well‐known pest control agent B. thuringiensis (Prabakaran and Hoti 2008; Adjallé et al. 2011) can be obtained by spray‐drying and currently it is reported as an economical process for formulation of probiotic bacteria (Chávez and Ledeboer 2007; Golowczyc et al.…”
Section: Discussionmentioning
confidence: 99%
“…2006). However, shelf‐stable and effective products of well‐known pest control agent B. thuringiensis (Prabakaran and Hoti 2008; Adjallé et al. 2011) can be obtained by spray‐drying and currently it is reported as an economical process for formulation of probiotic bacteria (Chávez and Ledeboer 2007; Golowczyc et al.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies related to the present work have specifically optimized the yield and particle size of spray dried particles [23][24][25][26]. Further work has examined the effects of spray drying process parameters on various species of bacteria [27][28][29]. Understandably, viral vectors, as considered in the present work, exhibit different stabilizing profiles than that of bacterial biologics and have not been included in previously published optimization studies.…”
Section: Introductionmentioning
confidence: 99%
“…According to Schnepf et al [32], depending on the protoxin composition, the crystals would assume various forms such as bipyramidal (Cry1), cuboidal (Cry2), flat rectangular (Cry3A), irregular (Cry3B), spherical (Cry4A and Cry4B), or rhomboidal (Cry11A) shapes. Employing response surface methodology, Adjalle et al [33] demonstrated a spray drying process for the raw solid-fermented matter from starch industry wastewater and wastewater sludge (after proper dilution) and showed that optimum solid particles in these media were 15 and 25 g/L, respectively, for maximum efficiency of drying. Since raw product (crystals, spores, and vegetative cells) is sufficient for field applications, without going through purification protocols, the filtrate of the fermented matter could directly be dried employing the method of Adjalle et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…Employing response surface methodology, Adjalle et al [33] demonstrated a spray drying process for the raw solid-fermented matter from starch industry wastewater and wastewater sludge (after proper dilution) and showed that optimum solid particles in these media were 15 and 25 g/L, respectively, for maximum efficiency of drying. Since raw product (crystals, spores, and vegetative cells) is sufficient for field applications, without going through purification protocols, the filtrate of the fermented matter could directly be dried employing the method of Adjalle et al [33]. This would benefit the farmers, especially from third world countries as envisaged by Anilkumar et al [7].…”
Section: Discussionmentioning
confidence: 99%